Metrics to Evaluate the Performance of Cancer Center Leadership: A Systematic Review. Issue 3 (May 2020) - Halpern, Michael T.; Gasoyan, Hamlet; Aaronson, William E.
Abstract : EXECUTIVE SUMMARY: Cancer centers are diverse healthcare organizations comprising clinicians and researchers dedicated to understanding, treating, and controlling cancer in the populations they serve. Although many metrics are used to evaluate cancer center performance, few of these standardized measures have been identified to evaluate cancer center leadership. We performed a systematic review to identify published literature presenting metrics used to evaluate the leadership of cancer centers. Metrics were then classified using 10 a priori–defined categories of evaluation. Overall, we reviewed 34 articles (studies, editorials, interviews). The most commonly discussed leadership evaluation category was Organizational Strategy/Planning (31 of the 34 articles), followed by Leader Characteristics (25 articles), Clinical Performance (21), and Facility Characteristics (20). Organizational Strategy/Planning metrics included governance structure, strategic development, quality assurance and improvement, mission and vision, business planning, and program development. Leader Characteristic metrics included communication, vision/strategic thinking, personal skills, team coordination, leadership style, and staff development. Clinical Performance metrics focused on delivery of and outcomes from clinical services, while Facility Characteristics included space allocation and access to support services. The metrics reviewed in this article may be considered measurable outcomes in evaluating whether cancer center leadership demonstrates key competencies. Additional research should explore the linkage among metrics used to evaluate cancer center leaders, desired competencies for healthcare leaders, and objective measures of whether a cancer center is successful.